ChemInform Abstract: A Mild and Efficient Synthesis of 2‐Oxazolines via Transamidation—Cyclodehydrosulfurization of Thioamides with 2‐Aminoethanol. Issue 14 (20th March 2013) - Goud, D. Raghavender; Pathak, Uma
Abstract The two‐step approach renders possible the preparation of oxazole derivatives bearing either aromatic or aliphatic substituents at C‐2 and may thus find an application in synthetic and medicinal chemistry.